Taxonomy and morphology of plant-parasitic nematodes associated with turfgrasses in North and South Carolina, USA - Zeng, Yongsan; Ye, Weimin; Tredway, Lane; Martin, Samuel; Martin, Matt (Zootaxa, 2012)
Twenty-nine species of plant-parasitic nematodes were recovered from 282 soil samples collected from turfgrasses in 19 counties in North Carolina (NC) and 20 counties in South Carolina (SC) during 2011 and from previous collections. These nematodes belong to 22 genera in 15 families, including Belonolaimus longicaudatus, Dolichodorus heterocephalus, Filenchus cylindricus, Helicotylenchus dihystera, Scutellonema brachyurum, Hoplolaimus galeatus, Mesocriconema xenoplax, M. curvatum, M. sphaerocephala, Ogma floridense, Paratrichodorus minor, P. allius, Tylenchorhynchus claytoni, Pratylenchus penetrans, Meloidogyne graminis, M. naasi, Heterodera sp., Cactodera sp., Hemicycliophora conida, Loofia thienemanni, Hemicaloosia graminis, Hemicriconemoides wessoni, H. chitwoodi, Paratylenchus goldeni, Xiphinema americanum sensu lato, X. bakeri, X. chambersi, Longidorus paralongicaudatus, and Aphelenchoides myceliophagus. Eleven species (Meloidogyne graminis, M. naasi, Cactodera sp., Pratylenchus penetrans, Hemicycliophora conida, Hemicaloosia graminis, Mesocriconema xenoplax, M. sphaerocephala, Ogma floridense, Paratrichodorus allius, Dolichodorus heterocephalus) were new records from turfgrass in both states; five (Heterodera sp., Loofia thienemanni, M. curvatum, Longidorus paralongicaudatus, Filenchus cylindricus) were new in SC; and three (Hemicriconemoides wessoni, Xiphinema bakeri, Aphelenchoides myceliophagus) were new in NC. The morphological and morphometric characteristics of these species are presented.